WHY THE NUMBER OF ADULT LEARNERS IS NOT GROWING - ATTITUDES OF LITHUANIAN ADULTS TOWARDS LIFELONG LEARNING - Zemaitaityte, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
This article analyzes the reasons that continue to encourage the way of a more active involvement of adults in lifelong learning in Lithuania.  Lithuania is characterized by an educated society that wants to advance, but Lithuania's Lifelong Learning (LLL) Index is one of the lowest in the EU. According to LSD data in 2019, Lithuanian LLL indicator was only 7%. Lithuania's Progress Strategy Lithuania 2030 and the National Progress Program 2014-2020 mention LLL as one of the most important strategic goals to be implemented at all levels and to cover all social areas. The education strategy for 2013-2022 aims to “mobilize not only the educational community, but also all Lithuanian people to study purposefully in order to achieve personal and national success. “(p. 11).  Recent research indicates that that although the main challenges hindering the growth of the number of adults participating in lifelong learning in Lithuania are financial barriers and the belief that learning is too late, and learning motivation is low, yet positive attitudes of Lithuanian adults towards lifelong learning, provide general expectation of increasing motivation for adult learning and more active involvement of adults in lifelong learning.